The Role of Village-Owned Enterprises in Improving Community Welfare in Gunungtawang Village, Selomerto District - Romandhon Romandhon; Bambang Agus Pramuka; Puji Lestari (UM Purwokerto Press, 2024)
Background : The village-owned enterprise ( BUMDes )